IMPLIKASI TEKNOLOGI DIGITAL TERHADAP MOTIVASI BELAJAR PAI DI MA MUHAMMADIYAH CURUP KECAMATAN CURUP TIMUR KABUPATEN REJANG LEBONG - Reni Dianti Rukmini; Rani Selviani; Muhammad Istan; Eka Apriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study aims to provide a comprehensive overview of the application of digital technology in the Islamic Religious Education (PAI) learning process at MA Muhammadiyah Curup, East Curup District, Rejang Lebong Regency. The background of this study stems from low student learning motivation in PAI subjects. The study was conducted using a qualitative approach using descriptive methods. The research subjects included students, PAI teachers, and the principal at MA Muhammadiyah Curup. Data were collected through interviews, observation, and documentation. The results indicate that the use of digital technology in PAI learning has become a crucial component in increasing student motivation and interest in learning. PAI teachers act as facilitators, motivators, spiritual guides, and innovators, able to optimize various digital media such as interactive PowerPoint presentations, learning videos, digital quiz applications, Google Classroom, and projectors to create a more engaging, varied, and modern learning environment. The application of this technology has been proven to increase student enthusiasm, encourage active involvement, and help them better understand PAI material. Keywords: Implications of Digital Technology, Learning Motivation, PAI, MTs. Muhammadiyah Curup